EFFECT OF LEVEL OF ENFORCEMENT OF KNEC RULES AND REGULATIONS ON THE PREVALENCE OF EXAMINATION MALPRACTICE IN PUBLIC AND PRIVATE SECONDARY SCHOOLS IN KISII COUNTY BETWEEN 2008 - 2014 - SHIBO, MARGARET NEKESA (Machakos University, 2019)
Examination malpractice in Kenya Certificate of Secondary Education examinations in Kisii County has been on the increase despite the strict enforcement of Kenya National Examinations Council (KNEC) rules and regulations that govern the exercise. This study set out to examine the effect of the level of enforcement of KNEC rules and regulations by invigilators on the prevalence of examination malpractice in Kisii County. This study employed ex post facto and survey research design. The target population comprised of 363 principals, 726 invigilators and 30 examination officers drawn from 317 public and 46 private secondary schools in Kisii County. A sample of 109 principals, 218 invigilators and 10 examination officials was selected through stratified random sampling. The study utilized questionnaires and interview schedules to collect both qualitative and quantitative data. Pearson Correlation Coefficient was computed using SPSS to analyze quantitative data. Qualitative data were analyzed thematically; related themes were summarized are reported in prose. The study found that level of enforcement of KNEC rules contributed to the high level of examination malpractice. Pearson correlation results were as follows: Level of enforcement of KNEC rules and regulations (r = 0.087; p = 0.275). The study recommended that: KNEC should consider engaging in extensive sensitization campaigns aimed at regularly reminding all concerned stakeholders and that, the school management should consider organizing prior assessments to check on compliance levels in respect of the set KNEC rules and regulations
Keywords: KNEC Rules and Regulations; Examination Malpractice; Kisii County